International organisations and human rights: What direct authority needs for its legitimation - Monika Heupel; Gisela Hirschmann; Michael Zürn (Review of International Studies, 2018)
Human rights violations by international organisations (IOs) are a possible side effect of their growing authority. Recent examples are the cases of sexual exploitation by UN peacekeepers and violations caused by IMF austerity measures. In response, IOs increasingly develop safeguards to protect human rights from being violated through their policies to regain legitimacy. We argue that this development can be accounted for by a mechanism we call `authority-legitimation mechanism'. We test this theoretical expectation against ten case studies on UN and EU sanctions policies, UN and NATO peacekeeping and World Bank and IMF lending. Next, we demonstrate inductively that the authority-legitimation mechanism can evolve through different pathways, depending on which actors get engaged. We label these pathways legislative institution-building if parliaments in member states put pressure on their governments to campaign for human rights safeguards in IOs, judicial institution-building if courts demand human rights safeguards, like-minded institution-building if civil society organisations, middle powers and IO bodies with little formal power push for human rights safeguards, or anticipatory institution-building if IOs adopt such safeguards from other IOs without having violated human rights themselves. Finally, we argue that which of these pathways are activated and how effective they are depends on specific conditions.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; international organizations; human rights; authority; legitimacy; legitimation